2002
DOI: 10.1075/aicr.35.33kle
|View full text |Cite
|
Sign up to set email alerts
|

The analogical foundations of creativity in language, culture & the arts

Abstract: The combinatoric problems associated with unrestricted models of human language processing suggest that real-world knowledge systems may have evolved in forms that make combinatoric processing problems linear. The role of Boolean groups and analogy in the extension and elaboration of complex behavioral systems, including natural language, suggests a theory that might account for the changes in human cognitive behavior that began in the Middle to Upper Paleolithic transition, and promises to continue through th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…In a series of works, S. Klein [36,37,38] has proposed a way of solving analogical proportion-like equations based on a so-called Appositional Transformation Operator or ATO (later named "Analogical Transformation Operators" [39]), denoted * , which is nothing but the strong binary equivalence: * ab is just a ≡ b. He observed that the repeated use of * allows him to obtain the solution which is less restrictive than the definition given in this paper.…”
Section: Boolean View Of Analogical Proportions: the Work Of J Piagmentioning
confidence: 99%
“…In a series of works, S. Klein [36,37,38] has proposed a way of solving analogical proportion-like equations based on a so-called Appositional Transformation Operator or ATO (later named "Analogical Transformation Operators" [39]), denoted * , which is nothing but the strong binary equivalence: * ab is just a ≡ b. He observed that the repeated use of * allows him to obtain the solution which is less restrictive than the definition given in this paper.…”
Section: Boolean View Of Analogical Proportions: the Work Of J Piagmentioning
confidence: 99%
“…On a more theoretical level, analyses of computational and artificial intelligence models suggest that the brain inherently must function algebraically (Marcus, 2001). It has been suggested more precisely that the findings derived from empirical research using a binary computational model can be seen as supporting Lévi-Strauss's algebraic model of mind (Klein, 2002). Likewise, some recent works using mathematical set notation show a general underlying algebraic structure for many myths and narratives (Griffin, 2006).…”
Section: The Algebraic Mindmentioning
confidence: 99%
“…Because of the requirement, for such systems, that "the freedom of the user to perform whatever action she desires must be balanced with the preservation of the storyline used to control the system's characters", they proposed narrative mediation, a technique "that exploits a plan-based model of narrative structure to manage and respond to users' actions inside a virtual world. He has researched analogical reasoning models (e.g., Klein 2002), and the generation of 3D virtual reality worlds using a meta-linguistic system, which can be configured to model a variety of theoretical linguistic models. Finally, we specify an architecture that uses these definitions to monitor and automatically characterize user actions, and to compute and implement responses to unanticipated activity."…”
Section: E Nissanmentioning
confidence: 99%